(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Light transmitting concrete is also named as translucent concrete, because of its transparent property. The main purpose is to use natural sunlight as a light source to reduce the power consumption of illumination and to use optical fiber to sense the stress of structure and also use this concrete for good aesthetic view of the building as architectural purpose. At many locations, the natural availability is compromised due to utilization of space in which case artificial lighting is required to be provided for most part of day also during the night. With depleting natural resources i.e. facilities available for generation of electrical power, utilization of natural light air by scientific construction methods becomes very important. The transparent concrete mainly focuses on transparency and its objective of application pertains to green technology and artistic finish. It is the combination of optical fibers and fine concrete. At present, green structures focus greatly on saving energy with indoor thermal systems. Therefore it is imperative to develop a new functional material to satisfy the structure in terms of safety monitoring, environmental protection and energy saving